A Low-Friction Capsule Robot with Drive–Control–Sensing Integration for Gastrointestinal Lesion Detection - Ziying Wang; Hang Yin; Zilin Wei; Shisheng Chen; Jiameng Li; Jingyao Sun; Wei Zhao; Yejuan Jia (Research)
pH and temperature in the gastrointestinal (GI) tract are correlated with many diseases, but patients suffer from the pain of traditional testing methods. Functionalized capsule robots for GI tract sensing offer a potential approach for early GI disease diagnosis. However, most capsule robots struggle with control and sensing integration. In addition, the friction encountered by capsule robots during navigation poses a challenge for their application. Here, a capsule robot with a low coefficient of friction is proposed to continuously detect pH and temperature. The hydrogel skin reduces the surface friction coefficient by more than 4 times and achieves an average propulsion speed of 12.79 mm s−1 in a living porcine small intestine. The capsule system enables continuous detection over a pH range of 2 to 8 and a temperature of 36 to 40 °C. We demonstrate capsule robots’ capability of multimodal locomotion through complex stomach and small intestine environment. It solves the problem that capsule robots used for sensing functions cannot be precisely controlled and achieves drive–control–sensing integration.